Identifying determinants of care for tailoring implementation in chronic diseases: an evaluation of different methods - Krause, Jane; Van Lieshout, Jan; Klomp, Rien; Huntink, Elke; Aakhus, Eivind; Flottorp, Signe; Straßner, Cornelia; Steinhäuser, Jost; Godycki-Cwirko, Maciek; Kowalczyk, Anna; Agarwal, Shona; Wensing, Michel; et al. (Implementation science, 2014)
The tailoring of implementation interventions includes the identification of the determinants of, or barriers to, healthcare practice. Different methods for identifying determinants have been used in implementation projects, but which methods are most appropriate to use is unknown.